Re-examining climate-driven Malthusian collapse in Kashmir: New palaeoenvironmental context for the archaeological record. (20th June 2022) - Spate, Michael; Penny, Dan; Yatoo, Mumtaz; Betts, Alison
Abstract: Previous syntheses of palaeoclimate and archaeological data from the Kashmir Valley have proposed that climate changes drove prehistoric settlement of the valley, based on the adaptation of West Asian winter crops to mid-Holocene warm-humid conditions ca. 5000 BP. It has been argued that these conditions enabled population growth that became unsustainable following the onset of a cold-arid phase ca. 3000 BP, with these cycles of growth and collapse again repeating ca. 2000 and 1000 BP. Here we present multi-proxy palynomorph, charcoal and sediment data indicating that from ca. 4500-1500 BP the environment of the valley was characterised by drier conditions, comparable to other regional records indicating weakening Westerly precipitation over Central Asia. Considering recent archaeobotanical data indicating the presence of both West Asian winter crops and East Asian summer millets in the valley as early as 4500 BP, we argue that rather than Malthusian cycles of growth and collapse in Kashmir, early populations likely drew on a broad range of available domesticates and varied ecotopes across the valley to allow a Boserupian response to changing Holocene climate conditions. These adaptations were likely more oriented towards flexible systems of agro-pastoralism practiced throughout the Inner Asian mountains, rather than towards developing large urban settlements as was the case in the river basins and plains south of Kashmir.